Investment problems and indigenous people a social-constructivist approach to law - Mutia Evi Kristhy; Ranti S Endah; Ronny Marthius Nababan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Investment problems and indigenous peoples occur by several factors, one of which is investment problems in the land sector. Given that land has an important meaning in investment, land policy is oriented to ease of investment. This study uses a normative research method with a Social-Constructivist approach. The results of the study show that the problems of investment and indigenous peoples in land are caused by several factors such as the determination of state policies in investment at the level of basic norms, national and national regulations, and including living law products in the areas where the indigenous peoples live.